Analysis of income and risks of the vaname shrimp business in Bratasena ponds, Tulang Bawang, Lampung - Wijayanto, Bambang Dwi; Buchori, Buchori; Rinnanik, Rinnanik (Institute of Computer Science (IOCS), 2024)
The research method used is field surveys and structured interviews with shrimp farmers. The collected data were analyzed using both quantitative and qualitative approaches. The analysis results indicate that income from vannamei shrimp business tends to be stable but is influenced by external factors such as price fluctuations and market conditions. On the other hand, risks such as shrimp diseases, climate change, and government regulations also affect the sustainability of this business. This research provides important insights for stakeholders in managing risks and enhancing the sustainability of vannamei shrimp business